2021
DOI: 10.1097/md.0000000000026693
|View full text |Cite
|
Sign up to set email alerts
|

The association between AST/ALT ratio and all-cause and cardiovascular mortality in patients with hypertension

Abstract: Previous studies had shown that an increased aspartate aminotransferase to alanine aminotransferase ratio (AST/ALT ratio) was associated with cardiovascular disease. This study aimed to assess the relationship between AST/ALT ratio and all-cause and cardiovascular mortality in patients with hypertension.By March 31, 2020, a cohort of 14,220 Chinese hypertensive patients was followed up. The end point was all-cause and cardiovascular death. Hazard ratios (HRs) and 95% CIs were calculated for mortality associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 33 publications
3
26
0
Order By: Relevance
“…The fact that in the multi-adjusted post-randomization model it tracked with γGT as an indicator of CV risk (Additional file 4 : Table S4) likely stands for a degree of liver dysfunction participating in the overall CV risk of the CANVAS population. Consistently, an association between AST/ALT ratio within the normal range and increased risk of all-cause and CV mortality has been previously reported in unselected populations with diabetes [ 41 ] and hypertension [ 42 ].…”
Section: Discussionsupporting
confidence: 77%
“…The fact that in the multi-adjusted post-randomization model it tracked with γGT as an indicator of CV risk (Additional file 4 : Table S4) likely stands for a degree of liver dysfunction participating in the overall CV risk of the CANVAS population. Consistently, an association between AST/ALT ratio within the normal range and increased risk of all-cause and CV mortality has been previously reported in unselected populations with diabetes [ 41 ] and hypertension [ 42 ].…”
Section: Discussionsupporting
confidence: 77%
“…A large sample cohort study with 14,220 participants examined the association between the AST/ALT ratio with ACM and cardiovascular mortality in hypertensive patients. This study found that an increased AST/ALT ratio was associated with increased risk of ACM (P value < 0.05) and cardiovascular mortality (P value < 0.05) in hypertensive patients 30 , after an average follow-up time of 1.7 years. Another study, based on the general population, followed 3494 participants for up to 10 years and found that the AST/ALT ratio increased with brain natriuretic peptide (BNP).…”
Section: Discussionmentioning
confidence: 62%
“…In addition, several studies have demonstrated that the AST/ALT ratio can be used as a risk predictor for cardiovascular diseases. In addition, several studies have shown that AST/ALT can be used as a risk predictor for cardiovascular disease 7,11,18,23 , nonalcoholic fatty liver 24 , hypertension 25 , obesity 26 , metabolic syndrome 27 , cognitive impairment 13 etc. The ALT/AST ratio may be more predictive of homeostatic model assessment for insulin resistance than the fasting insulin levels in nonobese, middle-aged, mixed-sex populations 17 .…”
Section: Discussionmentioning
confidence: 99%